(3bUI GdLGQjI JhOOs
(3ChdgG (B:s
(3MOKfG EHQGgje GdjeGfj QMeg Gddg JYGdi bGd(B: (3cGf HHZOGO eOI CejQ GdeDefjf gGQhf GdQTjO QLd s
(3BNQgG (B:s
(3aCfUQaJ GdLGQjI eY ehdGgG HSQhQ cKjQ, hEMSGf YXje s
(3Vef eLehY , JQJjHgG (B: (3ef U (B251 - (3U(B308s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B5 - (3U (B110 s
(3JHUQGJ GdCUd (B:s
(3HgG NQe s
Keywords: (3GdCOHs